PENGARUH AROMA TERAPI LEMON TERHADAP EMESIS GRAVIDARUM - Harahap, Novy Ramini; Rauda, Rauda; Nasution, Pratiwi; Syari, Mila; Pitriana, Dewi (Indonesian Trust Health Journal, 2022)
One of treatments in handling emesis gravidarum is aromatherapy essential oils such as citrus oil (orange, grapefruit, mandarin, lime, bergamot and grapefruit) safe and soft to use at this time. Solution four drops of the oil of choice which you prefer in the 5ml/1 teaspoon of the oil base, pour the bath, or pour two drops on a cotton round to breathe when you feel nausea. The study aimed to determine the influence of Lemon Aromatherapy against Emesis Gravidarum in the Erna Wati Clinic in Labuhanbatu District 2020.The study was Quasi Experiment with research two group pretest posttest with control group. The population was all pregnant women at Erna Wati Clinic of 22 pregnant women in first Trimester of gestational age of 1-12 weeks. The sample was 22 first Trimester pregnant women of gestational age of 1-12 weeks. Analysis of data used univariate and bivariate using wilcoxon test. The results showed the frequency of emesis gravidarum before being given aromatherapy the majority of mothers experienced nausea and vomiting 6 times were 9 respondents (40.9%), and after being given aromatherapy the majority of mothers experienced nausea and vomiting 2 times were 15 respondents (58.2%) with the results of the Wilxocon test (p-value=0.000). Conclusion showed the Influence of Lemon Aromatherapy against Emesis Gravidarum found in Erna Wati Clinic in 2020. It is recommended to pregnant women in order to get additional knowledge about Lemon aromatherapy against Emesis Gravidarum by looking for information from either print media or electronic media. Abstrak Salah satu penanganan yang dilakukan untuk menangani emesis gravidarum adalah aromaterapi minyak esensial seperti minyak sitrus (jeruk, jeruk mandarin, limau, bergamot dan grapefruit) aman dan lembut saat digunakan. Larutan empat tetes minyak pilihan dalam 5 ml / 1 sendok teh minyak dasar, tuangkan pada bak mandi, atau tuangkan dua tetes pada kapas bulat untuk dihirup saat merasa mual. Tujuan penelitian untuk mengetahui Pengaruh Aroma Terapi Lemon terhadap Emesis Gravidarum di Klinik Bidan Erna Wati Kabupaten Labuhanbatu Tahun 2020. Desain penelitian adalah Quasi Experiment dengan penelitian two group pretest posttest with control group. Populasi dalam penelitian ini adalah keseluruhan ibu hamil yang ada di Klinik Bidan Erna Wati Kabupaten Labuhanbatu Tahun 2020 sebanyak 22 ibu hamil Trimester I usia kehamilan 1-12 minggu. Sampel dalam penelitian ini berjumlah 22 ibu hamil Trimester I usia kehamilan 1-12 minggu. Analisa data menggunakan analisa univariat dan bivariat menggunakan uji wilcoxon. Hasil penelitian berdasarkan frekuensi emesis gravidarum sebelum diberikan aroma terapi mayoritas ibu mengalami mual dan muntah 6 kali sebanyak 9 responden (40,9%), dan sesudah diberikan aroma terapi mayoritas ibu mengalami mual dan muntah 2 kali sebanyak 15 responden (58,2%) dengan hasil uji wilxocon (p value = 0,000). Kesimpulan penelitian ini memperlihatkan bahwa ada Pengaruh Aroma Terapi Lemon terhadap Emesis Gravidarum di Klinik Bidan Erna Wati Kabupaten Labuhanbatu Tahun 2020. Disarankan kepada ibu hamil agar mendapatkan tambahan pengetahuan tentang Aroma Terapi Lemon terhadap Emesis Gravidarum dengan mencari informasi baik dari media cetak ataupun media elektronik.